Experiences and perceptions of dentistry graduates on the culmination of the thesis at a university in Peru - Castro-Rodríguez, Yuri (2021)
The university thesis represents an academic work where the student demonstrates the research learned skills; however, its completion requires specific skills and subject to limitations. Objective. To identify the perceptions of a group of dental graduates about their experiences while the undergraduate students develop their thesis. Methods. Phenomenological study that interviewed 32 students graduated from the Faculty of Dentistry (Universidad Nacional Mayor de San Marcos, Lima, Peru) through focus groups who successfully completed their degree thesis. The categories of personal, relationship and institutional factors were explored. The analysis was carried out inductively through opinions, search for similarities and synthesis of findings. Results. Three categories of analysis were found: personal, relational and institutional factors. Future job responsibility (personal factor) was perceived as one of the main stimulants to complete the thesis, the motivation of the thesis advisor (relational factor) was perceived as a characteristic that influenced completion while institutional support and data acquisition (institutional factors) were perceived as negative conditions and difficult to cope with. Conclusions. Various factors influence the completion of the university thesis such as: The motivation of the thesis topic, the support of the advisor and having resources to finance the execution were characteristics highlighted as factors that promote the development of the university thesis. These experiences are based on obtaining an academic degree to enter a labor system.